Global FMD epidemic situation in 2013-2015 and FMD control measures - D. A. Lozovoy; A. M. Rakhmanov (Ветеринария сегодня)
The paper gives official data on stringent foot-and-mouth disease epidemic situation existing in the world including Russia in 2013-2015 and on FMD control measures taken by the countries as well as on efficient use of FGBI «ARRIAH» manufactured FMD vaccines based on emergent FMDV strains.